Effect of section thickness on fatigue performance of laser sintered nylon 12. (August 2016) - Amel, Hoda; Rongong, Jem; Moztarzadeh, Hadi; Hopkinson, Neil
Abstract: Laser Sintering offers manufacturers freedom of design, which enables creating parts with complex geometries. However, very little investigation has been made into the effects of geometry on mechanical properties of the parts. In the present study, Laser Sintered Nylon 12 parts with different section thickness are subjected to displacement controlled tension-tension and force-controlled fully reversed fatigue loading to investigate the effect of geometry on their fatigue behavior. Section thickness of the parts is shown to have no significant influence on the fatigue behavior under tension only loading. However, fatigue life of parts under fully reversed loading is shown to increase with section thickness.